Risk factors and prevalence of tuberculosis, human immunodeficiency virus, syphilis, hepatitis B virus, and hepatitis C virus among prisoners in Pakistan - Kazi, Abdul M. (2010)
BACKGROUND: We evaluated the burden of sexual- or injection drug use (IDU)-related infections in male prisoners in Karachi, Pakistan. METHODS: We administered a structured questionnaire in a cross-sectional survey of 365 randomly selected imprisoned men. We analyzed blood for human immunodeficiency virus (HIV) and Hepatitis B and C by ELISA, and for syphilis by rapid plasma reagin and Treponema pallidum hemagglutination assay confirmation. Subjects with possible tuberculosis (WHO criteria) provided sputum samples for an acid fast bacillus smear and culture. RESULTS: Prevalence of tuberculosis was 2.2% (95%CI: 0.71, 3.8). HIV infected 2.0% (95%CI: 0.55, 3.4) of 357 randomly selected prisoners (8 refused to give blood), with confirmed syphilis in 8.9% (95%CI: 6.0, 11.8), hepatitis B virus in 5.9% (95%CI: 3.5, 8.3), and hepatitis C virus in 15.2% (95%CI: 11.7, 18.8). By self-report, 59.0% had used any illicit drugs, among whom 11.8% (95%CI: 8.5, 15.0) had injected drugs. The median length of stay in the prison had been 3.2 (range 1-72) months. CONCLUSIONS: All four infections were prevalent among the prisoners in Pakistan. Prisons are excellent venues for infectious disease screening and intervention given conditions of poverty and drug addiction. Collaboration with community-based health providers is vital for post-discharge planning.